The cognitive outcome in athletics among physical education teachers - Ismaiel, Ismaiel Ghasab; Oudat, Mo'een Ahmad; Thiyabat, Mohammad Khalaf; Alshdokhi, Khaled Abdullah (International Journal of Evaluation and Research in Education (IJERE), 2024)
The study aimed to identify the cognitive outcome in athletics for physical education teachers. The descriptive survey method was used and a cognitive test was applied as a measurement tool for data collection, which included 45 items for the fields of study: running, jumping, and throwing, and the study sample consisted of 198 teachers from Irbid First Directorate of Education in the first academic semester 2022/2023. The results showed that the level of the cognitive outcome in athletics for physical education teachers was "average" and that there were no statistically significant differences (α≤0.05) due to the effect of gender in all fields and all total scores, and the results of the study showed that there are significant differences Statistics in favor of more than 10 years experience.